1983
DOI: 10.1161/01.hyp.5.6_pt_3.v128
|View full text |Cite
|
Sign up to set email alerts
|

Basal levels of plasma epinephrine and norepinephrine in the dog.

Abstract: SUMMARY Conscious (n = 62) and anesthetized (n = 34) dogs were studied to establish basal levels and ranges for plasma epinephrine (E) and norepinephrine (NE) in this species. Trained conscious dogs were familiarized to recording conditions and personnel for 2 to 3 weeks and acclimatized to the laboratory for at least 15 minutes prior to blood sampling from a chronically implanted catheter. Their basal values were 65 ± 47 pg/ml for E and 145 ± 58 pg/ml for NE, which were significantly lower (p < 0.05) than val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

1986
1986
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 25 publications
1
3
0
Order By: Relevance
“…Therefore, the decrease in renal hemodynamics that we detected was relatively fixed and stable, compared with that determined in a study of dogs with hypertension induced by use of the 2K1C model. 20 In our study, mean (± SD) plasma NE concentration during the control period was 151.5 ± 28.3 pg/ml, which was similar to concentrations reported in studies of trained conscious dogs (145 ± 58 pg/ml 21 and 120 to 145 pg/ml 4 ). Analysis of these data suggests that dogs in the study reported here were trained and acclimatized sufficiently to the laboratory environment such that NE concentrations did not increase as a result of necessary manipulations.…”
Section: Discussionsupporting
confidence: 88%
“…Therefore, the decrease in renal hemodynamics that we detected was relatively fixed and stable, compared with that determined in a study of dogs with hypertension induced by use of the 2K1C model. 20 In our study, mean (± SD) plasma NE concentration during the control period was 151.5 ± 28.3 pg/ml, which was similar to concentrations reported in studies of trained conscious dogs (145 ± 58 pg/ml 21 and 120 to 145 pg/ml 4 ). Analysis of these data suggests that dogs in the study reported here were trained and acclimatized sufficiently to the laboratory environment such that NE concentrations did not increase as a result of necessary manipulations.…”
Section: Discussionsupporting
confidence: 88%
“…In these septic and non-septic controls catecholamine levels remained within, or very near, the normal range for anesthetized canines throughout the study. 19 However, we found that myocardial depression still occurred. In septic animals compared to non septic controls, profound highly significant drops in LVEF and significant worsening of circumferential strain and ventricular-aortic coupling occurred over two days, which occurred in the absence of increased endogenous and exogenous catecholamines.…”
Section: Discussionmentioning
confidence: 67%
“…After bacterial challenge (T0), in the absence of exogenous catecholamine administration, serial plasma epinephrine, norepinephrine, and combined catecholamine levels were within or slightly above the normal range for sedated otherwise healthy canines (Figure 2, Panel A-C). 19 Specifically, the only elevations in catecholamine levels above the normal range occurred in the plasma norepinephrine concentration of septic animals. In these animals, the elevations occurred transiently and were only minimally above the upper limit of normal (Figure 2, Panel B) for sedated animals.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation